2013
DOI: 10.3168/jds.2013-6670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early exposure to different feed presentations on feed sorting of dairy calves

Abstract: This study examined how early exposure to different feed presentations affects development of feed sorting in dairy calves. Twenty Holstein bull calves were exposed for the first 8 wk of life to 1 of 2 feed presentation treatments: concentrate and chopped grass hay (<2.5cm) offered ad libitum at a ratio of 7:3 as a mixture (MIX), or as separate components (COM). Calves received 8L/d of milk replacer (1.2kg of dry matter), with the amount progressively reduced after 5 wk to facilitate weaning by the end of wk 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
39
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 42 publications
7
39
3
Order By: Relevance
“…No differences in behavior were observed between SEP and MIX calves, which is contrary to previous findings in dairy calves, showing calves with a mixed ration spent more time feeding than calves with separate components (Miller-Cushon et al, 2013b). These authors also reported no differences in intake between these 2 feed presentation methods (Miller-Cushon et al, 2013a), which is in contradiction with the present study where SEP calves consumed more than MIX calves at 18, 19, 23, and 25 wk of age (Berends, 2014). The findings in the present study could relate to MIX calves receiving the composition selected by SEP calves in the previous week, which means they were a week behind in terms of composition.…”
Section: Discussioncontrasting
confidence: 99%
“…No differences in behavior were observed between SEP and MIX calves, which is contrary to previous findings in dairy calves, showing calves with a mixed ration spent more time feeding than calves with separate components (Miller-Cushon et al, 2013b). These authors also reported no differences in intake between these 2 feed presentation methods (Miller-Cushon et al, 2013a), which is in contradiction with the present study where SEP calves consumed more than MIX calves at 18, 19, 23, and 25 wk of age (Berends, 2014). The findings in the present study could relate to MIX calves receiving the composition selected by SEP calves in the previous week, which means they were a week behind in terms of composition.…”
Section: Discussioncontrasting
confidence: 99%
“…In calves, exposure to feed factors before weaning that encouraged greater sorting (such as feed presentation, Miller-Cushon et al, 2013a; and forage particle size, Miller-Cushon et al, 2013b) have been found to result in persistently greater sorting in the weeks after weaning. Further, differences in sorting resulting from early experience have been found to persist after transition to a novel ration in calves (Miller-Cushon et al, 2013a). The present results suggest that even short-term differences in feed experience during transition to a novel ration can influence the extent of feed sorting of a novel ration, at least in the initial week after transition.…”
supporting
confidence: 52%
“…Recent work has shown that differences in prior feed experiences can have persistent effects on feed sorting. For example, feed sorting in weaned dairy calves has been found to be influenced by prior exposure to different feed types (Miller-Cushon and DeVries, 2011), feed presentations (Miller-Cushon et al, 2013a), and ration forage particle sizes (Miller-Cushon et al, 2013b). Further, differences in feed sorting in weaned calves have been found to persist through transition to a novel TMR (Miller-Cushon et al, 2013a).…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward the end of the trial calves fed the MIX diet began to sort for short particles; a greater selection for short particles 3 wk after weaning may indicate a desire to consume more concentrate, the higher energy portion of the feed to support high growth demands in this stage (Drackley, 2008;Miller-Cushon and DeVries, 2011b). Although CON, SEP, and MIX calves were previously exposed to different feed treatments, no difference existed in sorting behavior of these calves postweaning, contrary to the findings of Miller-Cushon et al (2013), who found that, when given the opportunity to sort the ration at this time, calves will continue to do so postweaning.…”
Section: Discussionmentioning
confidence: 77%